2023
DOI: 10.1021/acs.chemrestox.2c00381
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Drug-Induced Liver Injury through Cell Morphology and Gene Expression Analysis

Vanille Lejal,
Natacha Cerisier,
David Rouquié
et al.

Abstract: Drug-induced liver injury (DILI) is a significant concern in drug development, often leading to drug withdrawal. Although many studies aim to identify biomarkers and gene/pathway signatures related to liver toxicity and aim to predict DILI compounds, this remains a challenge in drug discovery. With a strong development of high-content screening/imaging (HCS/HCI) for phenotypic screening, we explored the morphological cell perturbations induced by DILI compounds. In the first step, cell morphological signatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…Two other approaches with the potential to contribute to DILI prediction were released in 2023: one based on in vivo studies that capture mechanistic and phenotypic DILI information more reliably and accurately than other data sets, using in vivo liver histopathology nomenclature to provide a more informative and reliable data set for ML algorithms, and another using cell painting and transcriptomic data on compounds. This demonstrates the advantages of high-content imaging using transcriptomics data . These studies highlight the importance of combining different modalities for comprehensive toxicity assessments in drug discovery, such as integration of chemical and biological data, as mentioned by Liu et al .…”
Section: Advances In the Prediction Of Toxicity End Pointssupporting
confidence: 54%
See 1 more Smart Citation
“…Two other approaches with the potential to contribute to DILI prediction were released in 2023: one based on in vivo studies that capture mechanistic and phenotypic DILI information more reliably and accurately than other data sets, using in vivo liver histopathology nomenclature to provide a more informative and reliable data set for ML algorithms, and another using cell painting and transcriptomic data on compounds. This demonstrates the advantages of high-content imaging using transcriptomics data . These studies highlight the importance of combining different modalities for comprehensive toxicity assessments in drug discovery, such as integration of chemical and biological data, as mentioned by Liu et al .…”
Section: Advances In the Prediction Of Toxicity End Pointssupporting
confidence: 54%
“…This demonstrates the advantages of high-content imaging using transcriptomics data. 57 These studies highlight the importance of combining different modalities for comprehensive toxicity assessments in drug discovery, such as integration of chemical and biological data, as mentioned by Liu et al. 58 This multifaceted approach has the potential to lead to more robust predictive models, ultimately improving the safety and efficacy of new therapeutics.…”
Section: Advances In the Prediction Of Toxicity End Pointsmentioning
confidence: 99%
“…These datasets are valuable for diverse applications, including studies on 1) the compound MoA as illustrated by Lapins and Spjuth ( Lapins and Spjuth, 2019 ), Schneidewind et al ( Schneidewind et al, 2020 ), Wong et al ( Wong et al, 2023 ), Tian et al ( Tian et al, 2023 ), 2) target identification investigated by Akbarzadeh et al ( Akbarzadeh et al, 2022 ) and 3) linking cell morphology to disease studied by Cerisier et al ( Cerisier et al, 2023 ), Lejal et al ( Lejal et al, 2023 ). Moshkov et al ( Moshkov et al, 2023 ) demonstrated success in assessing gene function and Seal et al ( Seal et al, 2021 ; Seal et al, 2022 ; Seal et al, 2023a ) in evaluating environmental toxicants, which will be discussed in more detail throughout this review.…”
Section: Background On Cell Painting Molecular Representations and Ar...mentioning
confidence: 99%
“…Cellular morphology is a potentially rich data source for interrogating biological perturbations, especially at a large scale [9][10][11] . For example, Cellular morphological pro ling of compounds has been used to determine their mechanism of action 8,12,13 , identify their targets 14,15 , discover relationships with genes 16,17 , and characterize cellular heterogeneity 18 . Genes have been analyzed by creating pro les of cell populations in which the gene is perturbed by CRISRP and RNA interference (RNAi); these pro les have been used to represents the functional landscape of essential human genes [19][20][21] and identify genetic interactions 22,23 , or characterize cellular heterogeneity 24 .…”
Section: Introductionmentioning
confidence: 99%